Barriers To Healthcare Access: Examining Travel Time, Waiting Times, And Service Costs in Indonesia Primary Health Care - Purwito, Dedy; Linggardini, Kris; Jaitieng, Arunnee (Jurnal Berita Ilmu Keperawatan, 2025)
Access to primary health care in Indonesia faces significant challenges, including long travel times, high transportation costs, and poor quality of care due to a lack of health workers. These factors contribute to delays in treatment and increase the risk of severe health outcomes. Additionally, out-of-pocket expenses not covered by the national insurance program are major barriers, particularly for low-income families. To analyze the relationship between travel time, waiting time, transportation costs, service fees and access to health services. A cross-sectional study conducted in Banyumas district during May–June 2022 with 100 randomly selected adult respondents. Data were collected using a validated structured questionnaire consisting of six sections covering demographics, travel time, waiting time, transportation cost, service cost, and accessibility. Chi-Square test was used to examine relationships between the independent variables (travel time, transportation cost, service cost, and waiting time) and the dependent variable (healthcare accessibility). Travel time was significantly associated with access to health services (p = 0.041), as was waiting time (p = 0.035). However, transportation costs (p = 0.405) and service fees (p = 0.096) did not show a significant relationship. Improving transportation infrastructure and reducing waiting times through more staff and better service processes are key to enhancing healthcare access. Although transport and service costs were not statistically significant, they are still important for inclusive policy planning.